Enhancement of the Characteristics of Natural Ester in Transformer Oil Insulation using Nanofluids - A, Cianna; S, Sumathi; M, Ponmathy (Journal of Electronics and Informatics, 2023)
Oil is utilized in large transformers for its insulation properties and cooling. Mineral oil (MO) is not recyclable and it poses environment risks as it serves as insulation in transformer. It can be avoided by using a liquid coolant that has all the key qualities of transformer oil and seems to be biodegradable. Natural ester, made from plants as a substitute for mineral oil, has several profits. More investigations were conducted to improve the insulating liquid properties after the advent of nanofluids. In this study, a new hybrid method is employed to explore the properties by mixing different volume-percentage of hybrid nanomaterials with various natural esters. Evaluation of breakdown voltage and various transformer oil characteristics and results achieved showed that the hybrid nanofluid was essential in identifying a feasible alternative for mineral oil.